The Portrait of Noken As A Manifestation of The Existence of Papuans - Syufi, Yafed; Budiarsa, Made; Simpen, I Wayan; Sri Satyawati, Made (e-Journal of Linguistics; Vol 13 No 2 (2019): e-jl-July, 2019)
The Portrait of Noken as a manifestation of the Existence of Papuans is seen from the perspective of the socio-cultural aspect, Noken ,  as a manifestation of the indigenous Papuan representation in its mandate, is only vague but its meaning is very deep. Its meanings can be both denotative and connotative. For example, the Noken called mesin, as a medium of transporting various types of goods, has a denotative meaning. In addition, it also has a connotative meaning, namely a person who is open and likes giving whatever he/she has in his/her Noken . The next connotative meaning is as a mother who carries the burden of life or as it is usually called ifaj uk aromat mowran (a women carrying a lot of burden),  starting from the period of menstruation, conceiving, giving birth and breastfeeding, which is identical to a Noken called mesin . Unlike the case of Noken , which is called mecoi , this kind of Noken has two kinds of meanings, namely denotatively as a means of transporting goods and connotatively as a person who is closed or stingy. Both mesin and mecoi are used for reducing the amount of garbage that has been wrapped around the life of the nation and the state.